(3EOGQI GdehGQO GdHTQjI aj GdNOeI GdeOfjI (B/s - (3GdcHjSj, YGeQ NVjQs ((3GdbGgQI(B: s (3GdefXeI GdYQHjI ddJfejI h GdGOGQI(B, s, 2010)
(3fTCI h JWhQ GdOhQ GdGSJQGJjLj dGOGQI GdehGQO GdHTQjI , OQGSI GdhXGFa GdYGeI h JMdjdgG h JWhjQgG , GdJNWjW ddbhi GdYGedI aj GdefXeGJ GdYGeI , GdGNJjGQ h GdJYjjf aj GdNOeI GdeOfjI (B: (3GdNWhGJ h GdTQhW GOGQI GdeSGQ GdhXjaj (B: (3GdJQbjGJ h GdJfbdGJ , SjGSGJ GdOaY (B: (3GdQGJH h GdCLhQ , Jbjje COGA GdYGedjf aj GdNOeI GdeOfjI , GOGQI HQGeL GdMeGjI h GdQYGjI h GdJfejI , fXe eSGAdI GdYGedjf HGdNOeI GdeOfjI h SjGSGJ h GdJRGeGJ EfgGA NOeI GdYGedjf(B.s
(3agQS GdGTcGd U(B.(3`` e `` ,;agQS GdLOGhd U(B.(3`` f ``s
Keywords: (3GdGOGQIs; (3GdehGQO GdHTQjIs; (3GdehGQO GdHTQjIs